England and the Thirty Years' War - Marks, Adam (History of warfare, 2023)
"The Thirty Years' War (1618-1648) was a significant and traumatic event in the history of Europe. Based upon original archival research conducted across European archives, this book discusses both the successes and failures of the early Stuarts' foreign policy. It sheds new light on the Spanish match, reassesses the military capacity of the Stuart state in the run up to the Civil War and fundamentally challenges the idea that there was little or no engagement by England with the Thirty Years' War"--